The Knockdown of USP34 Inhibits the Progression of Hepatocellular Carcinoma by Accelerating c-Myc Degradation - Liu, Hailiang; Wei, Xile; Nie, Ye; Liu, Jianshan; Fan, Ming (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The function and mechanism of ubiquitin-specific protease 34 (USP34) in hepatocellular carcinoma (HCC) were explored to provide new molecular targets for treating HCC. Materials and Methods: In the present study, bioinformatics techniques, quantitative real-time polymerase chain reaction, and western blot were used to detect the level of USP34 in HCC tissues and cell lines. Small interfering RNA of USP34 was transfected into HCC cells, and then Cell Counting Kit-8 (CCK-8) assay, wound healing assay, and transwell assay were performed to verify the proliferation, migration and invasion of HCC cells. Enzyme-linked immunosorbent assay was utilized to assess the glycolysis level in HCC cells. Co immunoprecipitation was used to evaluate the ubiquitination level of cellular Myc (c-Myc). Results: The expression of USP34 was upregulated in HCC patients and strongly associated with worse outcomes. Meanwhile, interference with USP34 suppressed the proliferation, migration, and invasion of HCC cells. In addition, silencing of USP34 reduced the glucose uptake, lactate production and ATP content in HCC cells, as well as downregulated the expression levels of glycolysis-related proteins (hexokinase 2, glucose transporter 1, pyruvate kinase M2, and lactate dehydrogenase A). Furthermore, the knockdown of USP34 enhanced the ubiquitination level of c-Myc and increased the degradation of c-Myc. Overexpression of c-Myc reverted the inhibitory effects of si-USP34 on the malignant biological behavior in HCC cells. Conclusion: The USP34 regulates aerobic glycolysis and inhibits the progression of HCC by accelerating c-Myc ubiquitinated degradation. Cite this article as: Liu H, Wei X, Nie Y, Liu J, Fan M. The knockdown of USP34 inhibits the progression of hepatocellular carcinoma by accelerating c-myc degradation. Turk J Gastroenterol. 2025;36(9):573-582.